Fuzzy Set-Based Approaches in Wind Energy Research: A Literature Review - Cem, Ecem; Cebi, Selcuk (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Wind energy is gaining significance in the context of evolving sustainability and energy policies. According to GWEC Market Intelligence's forecast, an annual addition of 136 GW is anticipated from 2023 to 2027, reaching a total of 680 GW. The optimistic outlook extends to 2030, surpassing prior projections by 13%. This revision reflects the continuous and escalating potential of wind energy, affirming its pivotal role in the ever-evolving landscape of sustainability and energy policies. With the growing popularity of wind energy, there is a noticeable increase in the number of studies conducted in this field. This study aims to investigate the application of fuzzy methods in the field of wind energy research. The research provides detailed answers to questions about how fuzzy methods are used to address wind energy problems and why they are chosen. Fuzzy logic proves effective in handling uncertainties in wind energy problems and offers solutions to complex issues in this field. A comprehensive literature review indicates that fuzzy methods, along with hybrid approaches, are becoming popular in wind energy studies.
Keywords: Fuzzy Methods; Wind Energy; MCDM; DECISION-MAKING; SELECTION; LOCATION; SOLAR; Computer Science; Mathematics